PHYSIOLOGICAL STUDIES ON THE CARDIOPULMONARY INDEX CHANGES IN ADAPTATION TO PROGRESSIVE PHYSICAL LOADS - Kupriyanov, S. V.; Bochkarev, S. V.; Semenova, L. M.; Kruglikov, N. Yu.; Myasnikova, I. A.; Nizova, D. I.; Zhuravleva, N.V.; Mohammad, Alhasan (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Objective. The main purpose of the research was to develop a coefficient of cardiorespiratory system status, which will take into account both frequency and power characteristics of external respiration and hemodynamics activity. Compare an informativeness of this coefficient with a universally accepted Hildebrandt one.Materials and Methods. 154 apparently healthy young people of both sexes were examined. On a bicycle ergometer with a pedaling rhythm of 40 per minute, five standard stages of short-term physical exercise load ranging from negligible to moderate were provided. Spirography, tonometry and pulsometry were carried out before loading, at its peak and after it. The parameters specified were recorded for each subject simultaneously. Systolic volume was calculated using Starr formula with subsequent defining cardiac minute output.Statistical analysis was performed using Statistica ® 7.0 package (StatSoft Inc., USA). Assessment of results’ significance was calculated using Student's t-test and sign test.Results. In the case of low short-term physical exercises pulmonary ventilation is increased due to greater reactivity of external breathing amplitude and to a lesser extent due to change in the frequency of respiratory movements. This type of reactions of the respiratory component in cardiorespiratory interaction is more efficient. In the given conditions, body’s adaptation is ensured by breathing component dominance, while responses of systemic arterial pressure and pulse turn out to be less pronounced, less stabile. Taking into account greater adaptive importance in power characteristics changes of respiratory and cardiovascular activity, a coefficient of cardiorespiratory system status is proposed – MBV/RMV (ratio of minute blood flow volume to respiratory minute volume). The given factor is demonstrated to have significantly greater informative value and sensitivity to generally recognized Hildebrandt coefficient.